PENGARUH MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP PEMAHAMAN KONSEP KELAS IV SD INDERALAYA - reny, fenia (Program Studi Pendidikan Guru Sekolah Dasar Universitas Katolik Musi Charitas, 2018)
The problem in this research is whether there is influence of cooperative learning model type Numbered Heads Together (NHT) to student learning outcomes in grade IV SD Negeri 5 Inderalaya. The purpose of this study is to determine the effect of the model of learning Numbered Heads Together (NHT) on the results of learning mathematics students in grade IV SD Negeri 5 Inderalaya. The population of this research is the students of class VI SD 5 Inderalaya which amounted to 71 people. The sample of students in grade IVB is 37 people. Research method of quasi-experimental design of one group pretest posttest design research. Technique Data collection used is test. The data obtained were analyzed using the t-test. Based on result of t-test analysis for final test at significant level α = 0,05 obtained  thitung > ttabel  (thitung =17.40 >  ttabel = 2,02), so it can be concluded there is influence of cooperative learning model type Numbered Heads Together (NHT) Studying Student Math In Class IV SD Negeri 5 Inderalaya.